Windowns server 2003 networkinastructure - J.C Mackin (Microsoft Press, 2006)
Announcing an all-new MCSA/MCSE Training Kit designed to help maximize your performance on Exam 70-291, a core exam for the new Windows Server 2003 certification. This kit packs the tools and features that exam candidates want most—including in-depth, self-paced training based on final exam content; rigorous, objective-by-objective review; exam tips from expert, exam-certified authors; and a robust testing suite. It also provides real-world scenarios, case study examples, and troubleshooting labs for skills and expertise that you can apply to the job.